2004
DOI: 10.1111/j.1348-0421.2004.tb03483.x
|View full text |Cite
|
Sign up to set email alerts
|

Differential Susceptibility of Cells Expressing Allogeneic MHC or Viral Antigen to Killing by Antigen‐Specific CTL

Abstract: Cytotoxic T lymphocyte (CTL)3 markers (i.e., perforin and Fas ligand) are always present in biopsies of tissues undergoing rejection but are absent in those of nonrejected tissue (35). Allo-antigen-specific CTLs can be isolated from allografts being rejected but not from biopsies that show no rejection (9). The adoptive transfer of alloreactive CTLs into SCID mice can cause allograft rejection and the adoptively transferred CTLs can be recovered from grafts undergoing rejection (41). Similarly, in several well… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
16
0

Year Published

2006
2006
2014
2014

Publication Types

Select...
6
1

Relationship

5
2

Authors

Journals

citations
Cited by 15 publications
(16 citation statements)
references
References 52 publications
0
16
0
Order By: Relevance
“…The presence of allograft-induced macrophages (H-2 b ) results in the apoptotic death of H-2 d allografts (e.g., Meth A cells and BALB/c skin) with MHC haplotype (H-2 d ) specificity, which occurs in a Ca 2ϩ -and cell-cell contact-dependent, but Fas-, perforin-, and soluble factor-independent manner (9,(15)(16)(17)(18)(19)(20)(21)23). The macrophages are inactive toward donor-type Con A blasts (8,15).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…The presence of allograft-induced macrophages (H-2 b ) results in the apoptotic death of H-2 d allografts (e.g., Meth A cells and BALB/c skin) with MHC haplotype (H-2 d ) specificity, which occurs in a Ca 2ϩ -and cell-cell contact-dependent, but Fas-, perforin-, and soluble factor-independent manner (9,(15)(16)(17)(18)(19)(20)(21)23). The macrophages are inactive toward donor-type Con A blasts (8,15).…”
Section: Discussionmentioning
confidence: 99%
“…In contrast, allograft-induced T cells are highly cytotoxic against donor-type Con A blasts, mastocytoma (e.g., P815) cells, lymphoid (e.g., P388D1 and L1210) tumor cells, and some fibroblastic (e.g., BALB/3T3 and Colon26) cells. Unexpectedly, however, the anti-H-2 d CTLs are inactive toward epithelial (e.g., BALB/c skin component) cells, squamous cell carcinoma (e.g., KLN205) cells, and fibrosarcoma (e.g., Meth A) cells (20). Noguchi et al (10) also reported that Meth A cells were a CTL-resistant cell line.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The allograft (H-2 d )-induced macrophages (H-2 b ) exhibited cytotoxic activity against BALB/c (H-2 d ) skin components, KLN205 squamous carcinoma (H-2 d ) cells, and Meth A (H-2 d ) fibrosarcoma cells; whereas they were inactive toward donor (H-2 d )-type concanavalin A blasts. In contrast, allograft (H-2 d )-induced CTLs (H-2 b ) were cytotoxic against the donor (H-2 d )-type lymphoblasts, lymphoid tumor (e.g., P388D1 and L1210; H-2 d ) cells, mastocytoma (e.g., P815; H-2 d ) cells, and some fibroblastic (e.g., Colon26 and BALB/3T3; H-2 d ) cells; whereas they were inactive toward BALB/c skin components, KLN205 squamous carcinoma cells, and Meth A fibrosarcoma cells (Yoshida et al, 1997a,b;Lee et al, 2004;Yamaguchi et al, 2005). Unexpectedly, the infiltration by AIM preceded that by CTLs by several days during the course of the allograft rejection (Yoshida et al, 1997a).…”
Section: Introductionmentioning
confidence: 99%
“…In contrast, allograft-induced CTLs were found to be highly cytotoxic against donor (H-2 d )-type Con A blasts, mastocytoma (e.g., P815) cells, lymphoid (e.g., P388D1 and L1210) tumor cells, and some fibroblastic (e.g., Balb/3T3 and Colon26) cells. Unexpectedly, however, they were inactive toward epithelial (e.g., BALB/c skin component) cells, squamous cell carcinoma (e.g., KLN205) cells, and fibrosarcoma (e.g., Meth A) cells, although all these cells could block the recognition of allogeneic targets by CTL in cold target inhibition assays (13). Taken together, the data suggest that cells expressing allogeneic major histocompatibility complex (MHC) class I molecules show differential susceptibility to the CTLs and macrophages in a cell type-dependent and MHC class I antigen (or haplotype)-specific manner.…”
mentioning
confidence: 98%